Ediacaran tectographs from the Itajaí Basin: A cautionary tale from the Precambrian - Becker Kerber, B.; Prado, G. M.E.M.; Archilha, N. L.; Warren, L. V. [UNESP]; Simões, M. G. [UNESP]; Lino, L. M.; Quiroz-Valle, F. R.; Mouro, L. D.; El Albani, A.; Mazurier, A.; Paim, P. S.G.; Chemale, F.; et al. (Elsevier, 2024)
Simple and horizontal trace fossils from the Ediacaran Period (635–538.8 Ma) compose some of the oldest evidence for the presence of metazoans in the Proterozoic fossil record. Unfortunately, various abiotic processes may produce similar structures on sedimentary beds. One of the oldest records of the Ediacaran biota from Western Gondwana is preserved in the Itajaí Basin (SE Brazil), a peripheral foreland basin related to the Dom Feliciano Belt. The fossil assemblage in the Itajaí Basin consists of Aspidella, Nimbia, microbially induced sedimentary structures (MISS), and problematic taxa, including filamentous body fossils. Moreover, foreland basins are characterized by thrust-related fold belts, a result form their compressive tectonic settings. Here we report a new occurrence of enigmatic repeated horizontal markings. These structures exhibit linear to looping markings that are strikingly similar to simple horizontal animal trace fossils. However, the repetitive, preferentially oriented morphologies, and direct association with clasts show that they are tectographs, a rare pseudofossil interpreted to be formed by tectonically-induced bed-to-bed shearing. Indeed, their preferential alignment (NW-SE), following the original tectonic stress field associated with the development of the Itajaí Basin, strongly supports this interpretation. Considering the tectographs from North Carolina slate belt and Kupferschiefer of Germany, the Itajaí Basin structures are the third occurrence worldwide of such pseudofossils and the first case for Ediacaran successions, exhibiting a clear relationship to the tectonic setting associated with Western Gondwana assembly. Hence, some criteria to evaluate putative trace fossils are proposed, and we suggest that caution is needed when dealing with sedimentary structures that are candidates to be produced by metazoan activity in the deep time. This cautionary tale is valuable for Precambrian and Paleozoic paleontologists and geologists with implications for future astrobiological studies.
Keywords: Biogenicity; Early animals; Pseudofossils; Trace fossils